FEATURES OF CLOTHING HEAT BALANCE CALCULATION UNDER HIGH TEMPERATURES - Mirtalipova Nargiza Khasankhodzhaevna; Kamilova Khalida Khafizovna (International Journal of Innovations in Engineering Research and Technology, 2023)
The basis of the hypothesis about the need to select clothes for workers in terms of heat resistance depending on energy consumption when performing work at different temperatures of the air while maintaining the heat balance is outlined.